Production of Kombucha with NZ Honeydew Honey - Quach, Edward (Auckland University of Technology, 2020)
Kombucha is a fermented tea drink using a Symbiotic Culture of Bacteria and Yeast (SCOBY) which is receiving increased research and development interest due to its increasing popularity, large market share in the beverage industry and numerous beneficial health claims. Typical kombucha utilises green or black teas as the base media with sucrose as the substrate for fermentation. In this study, a novel kombucha beverage utilising Tie Guan Yin (TGY), a Chinese oolong tea, and honeydew honey as a substrate for fermentation was developed. 2L of tea sweetened with 150g of honeydew honey was fermented using 50g of SCOBY at ambient temperature (20-25°C). TGY tea was selected for its complex aroma and flavour profile as well as the lack literature documenting the use of oolong teas for producing kombucha. Honeydew honey was selected for its high antioxidant activity, amino acid content and presence of oligosaccharide sugars. The titratable acidity and concentration of kombucha’s primary metabolites were assessed over the course of the fermentation period. The titratable acidity of the honey kombucha increased from 0.016 ± 0.003% acetic acid equivalent (ACE) on day 0, to 0.599 ± 0.0582% ACE after 14 days of fermentation. This was significantly higher than the titratable acidity from kombucha made from sucrose which increased from 0.011±0.007% ACE on day 0, to 0.199 ± 0.087% ACE after 14 days. This indicated that honeydew honey can accelerate the kombucha fermentation process when compared to sucrose as the substrate. The primary kombucha metabolites consist of ethanol, acetic acid and gluconic acid. The concentration of these compounds increased with fermentation time and reached (in g/L kombucha) 1.325±0.469, 4.191±0.828, 4.890±1.256 for ethanol, acetic acid and gluconic acid respectively after 14 days of fermentation. In the case of ethanol, the concentration was below the 0.5% ABV threshold set by the New Zealand Ministry of Primary Industries, which allows the kombucha to be labelled as a non-alcoholic beverage in New Zealand. The antioxidant activity was measured using three assays: phosphomolybdenum, ferric-ion reducing antioxidant power (FRAP) and cupric reducing antioxidant capacity (CUPRAC). All three assays showed that the antioxidant activity of the kombucha increased with fermentation time. The total phenolic content, determined using Folin-Ciocalteu reagent, also showed an increasing trend to increase with fermentation time. The amino acid composition of the honeydew honey was predominantly proline; however, alanine, valine, leucine, isoleucine, phenylalanine, glutamic and aspartic acids were also detected. The concentration of all amino acids was found to decrease once the kombucha ferments. This is likely due to the amino acids being metabolised by the microorganisms in the SCOBY. The sugar composition of the honeydew honey and kombucha was assessed. Glucose, fructose, maltose and melezitose were detected in the kombucha along with potentially palatinose and turanose. The glucose and fructose concentrations decreased with fermentation time as they are metabolised by the bacteria in the SCOBY. Melezitose, palatinose and maltose did not show any changes in concentration with fermentation time, indicating they are not metabolised by the bacteria and yeasts in the kombucha. Microbiology analysis was carried out to identify the species of bacteria found in kombucha and to quantify their concentrations in the kombucha drink. DNA genomic sequencing on kombucha and SCOBY culture from the honey kombucha was conducted to elucidate the bacteria found in kombucha. The predominant species of bacteria found in the SCOBY were komagataeibacter and gluconobacter species which combined to make up over 80% of the DNA sequenced in the samples. Plate count experiments quantified that bacteria cultured on agar plates increased with concentration with fermentation time, reaching 6.86 log(colony forming units/mL kombucha) which is above threshold criteria for a food to be considered probiotic. However, due to time constraint identification and DNZ sequencing of fungi and yeast in the honey kombucha were not carried out. This thesis provides a comprehensive study on a kombucha beverage produced from TGY and honeydew honey. Solid foundations were also laid for further research into discerning the oligosaccharide composition of honeydew honey and kombucha microbiology analysis.
Keywords: Kombucha; Honeydew honey; Oligosaccharides; Titratable acidity; Antioxidant activity; Total phenolic content; Amino acids; Kombucha metagenomics; Carbohydrates; Organic acids; Tie guan yin; Ethanol; Gluconic acid; Colour